Pendekatan Interdisipliner dalam Studi Agama Islam - Ikhsan, Amirul; Chotimah, Chusnul; Syaifullah, Muhammad (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2023)
The development of an increasingly advanced era has had an impact on various dimensions of human thought. In the context of Islam, there are indications that understanding of Islam cannot only be limited by one approach or scientific field, but requires various approaches based on various scientific disciplines. Therefore, an interdisciplinary approach is important. In Islamic studies, the approaches used include history, philosophy, sociology, religious anthropology, and other disciplines. Along with efforts to understand Islam, this religion has experienced a very significant development.